Catalogue of immature hominin fossils from the University of the Witwatersrand, South Africa - Debra R. Bolter; Bernhard Zipfel (Annals of Human Biology, 2025)
Background: This study evaluates the fossil remains of South African hominins curated at the University of Witwatersrand Johannesburg (Wits University), the largest repository of human evolution assemblages in southern Africa.Aim: The aim of the study was to identify immature specimens within the assemblage as a resource for paleoanthropologists in understanding developmental adaptations in Plio-Pleistocene hominins.Subjects and methods: Data were compiled from curatorial catalogues, visual inspections, unpublished notes, and published site-specific inventories. The assessment classified specimens as “Pre-Adult” based on dental, cranial, and postcranial maturity indicators, following established methodologies.Results: Of the 3,277 catalogued specimens in the Wits hominin collections, 650 entries (19.8%) were identified as immature, representing three genera: Australopithecus, Paranthropus, and Homo. These findings were analysed by site, element type, and specimen associations. Notable insights include pre-adult remains of Australopithecus from Malapa, Sterkfontein and Makapansgat, Paranthropus from Drimolen and Kromdraai, and Homo from Rising Star. The variability in accessioning practices, fragmentary preservation, and ongoing research influenced the completeness of the inventory, highlighting challenges in catalogue standardisation and fossil classification.Conclusions: This comprehensive catalogue of immature fossils provides a critical resource for investigating morphological variation, life history traits, and evolutionary adaptations across hominin genera. It underscores the significance of South African fossil collections in exploring developmental patterns and evolutionary pathways leading to the extended life cycle characteristic of Homo sapiens.